Defense Mechanisms and Borderline Personality Organization Among COVID-19 Believers and Non-believers During Complete Lock-Down - Zajenkowska, Anna; Nowakowska, Iwona; Bodecka-Zych, Marta; Rajchert, Joanna; Kaźmierczak, Izabela; Jakubowska, Adrianna; Pinkham, Amy E. (Frontiers in Psychiatry, 2021)
The aim of the current study was to investigate whether a specific social perception of the pandemic – believing or not in COVID - predicts borderline personality organizations and whether this relationship is mediated by more primitive maladaptive mechanisms – splitting, denial, and dissociation. The online study included 720 volunteers aged 25-45. Participants were diverse in terms of place of residence, being in a relationship, and education level. Approximately 30% of the general population reported not believing in the COVID pandemic. Non-believers had more severe borderline personality organization and used more maladaptive defense mechanisms than believers. Individuals, who deny COVID-19 are more likely to show characteristics of borderline personality disorder. Splitting is an important mechanism in this relationship.